Репрезентація архітектурної спадщини Сіверщини у Великій українській енциклопедії - Вечерський, В.В. (Сіверщина в історії України, 2020)
Стаття присвячена проблематиці репрезентації архітектурної спадщини Сіверщини як важливого історичного регіону України
у Великій українській енциклопедії – державному енциклопедичному
проекті, що реалізується з 2013 р. як енциклопедія універсального
характеру у вигляді багатотомного видання і одночасно – веб-порталу. Опрацьовано методику та критерії відбору гасел (статей) з
цієї тематики з особливим акцентуванням необхідності дотримання балансу між універсальним, національним і регіональним. Запропоновано методичні принципи та критерії включення до універсальної енциклопедії гасел (статей) про архітектурні пам’ятки, у т. ч. і
втрачені, біографічних гасел про творців цих пам’яток та мінімально необхідних термінологічних гасел, без яких вищезазначена інформація буде «нечитабельною» для користувачів. The article is devoted to the problem of representation of the
architectural heritage of the Siver region as an important historical region
of Ukraine in the Great Ukrainian Encyclopedia - a state encyclopedic
project implemented since 2013 as an encyclopedia of universal nature in
the form of a multi-volume publication and at the same time a web portal.
The methodology and criteria for the selection of slogans (articles) on this
topic were elaborated, with the emphasis on the need to strike a balance
between universal, national and regional. It is especially interesting to
trace it in the aspect of regional research, at least on the example of Siver
region. According to the analysis of the literature, the actual problems of
representation of architectural monuments of historical regions of Ukraine
in encyclopedic editions of universal character have not been theoretically
elaborated yet. Against this background, there are three main groups in
the systematization of encyclopedic slogans: architectural monuments;
biography; terminology (general concepts). You can only distinguish
landmarks from rank and file expertly. The encyclopedia includes reference
articles about architects – authors of architectural monuments, who started
new architectural schools, new stylistic trends in architecture, embodied
innovative solutions in the fields of architectural typology, structures,
aesthetics, which had universal or national significance, made a mark.
architectural science. This is done on the recommendation of experts.
Distinguishing between the terms special and narrow is a difficult task,
the solution of which requires both deep professional knowledge and a
broad general erudition. Therefore, the selection of slogans took into
account a number of criteria listed in the article. The article proposes
the methodological principles and criteria for inclusion in the universal
encyclopedia of slogans (articles) on architectural monuments, including
lost, biographical slogans about the creators of these monuments and
the minimum necessary terminological slogans, without which the above
information will be «unreadable» for users.